Integrated compounding and injection moulding of short fibre reinforced composites - Sousa, R. A. (2004)
Composites of high density polyethylene (HDPE) and carbon fibre (C fibre) were compounded and moulded into tensile test bars in compounding injection moulding (CIM) equipment that combines a twin-screw extruder and an injection moulding unit. Two HDPE grades exhibiting different rheological behaviours were used as matrices. The mechanical properties of the moulded parts were assessed by both tensile and impact tests. The respective morphologies were characterised by scanning electron microscopy (SEM) and the semicrystalline structures of the matrices investigated by X-ray diffraction. The final fibre length distribution and fibre orientation profiles along the part thickness were also quantified. The composites with lower viscosity exhibit higher stiffness, higher strength and superior impact performance. Both composites exhibit a three layer laminated morphology, featuring two shell zones and a core region. Interfacial interaction is favoured by a lower melt viscosity that enhances the wetting of the fibre surfaces and promotes mechanical interlocking. The composites display a bimodal fibre length distribution that accounts for significant fibre length degradation upon processing. The dimensions of the transversely orientated core differ for the two composites, which is attributed to the dissimilar pseudoplastic behaviour of the two HDPE grades and the different thermal levels of the compounds during injection moulding. Further improvements in mechanical performance are expected through the optimisation of the processing conditions, tailoring of the rheological behaviour of the compound and the use of more adequate mould designs